2016
DOI: 10.1111/ggi.12721
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of personalized medicine for fracture risk assessment in osteoporosis

Abstract: The present review summarizes our efforts to identify genetic polymorphisms associated with osteoporotic fractures and to establish a genetic risk score (GRS) to predict fracture risk in consecutive Japanese autopsy cases carried out at Tokyo Metropolitan Geriatric Hospital between 1995 and 2011. Three single nucleotide polymorphisms in transforming growth factor β-1, rs1800470; thrombospondin, type 1, domain-containing 7A, rs12673692; and formiminotransferase N-terminal subdomain-containing gene, rs7605378, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 87 publications
0
5
0
Order By: Relevance
“…Taken together, this confirms that trabecular and cortical microtraits are differentially and independently modulated. These findings underscore the importance of precision phenotyping in mapping and in experimental precision medicine …”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Taken together, this confirms that trabecular and cortical microtraits are differentially and independently modulated. These findings underscore the importance of precision phenotyping in mapping and in experimental precision medicine …”
Section: Discussionmentioning
confidence: 69%
“…These findings underscore the importance of precision phenotyping in mapping and in experimental precision medicine. (82,83) Advantages and limitations This is one of the first genetic studies of bone microarchitecture in mouse using μCT. Our method provides a precise way to quantify and image microarchitecture in trabecular and cortical bone compartments with a resolution of 10 microns or less.…”
Section: Site Specificitymentioning
confidence: 99%
“…Taken together, this confirms that trabecular and cortical bone microtraits are differentially and independently modulated. These findings underscore the importance of precision phenotyping and in mapping and in precision medicine (117,118) .…”
Section: Site Specificitymentioning
confidence: 64%
“…Thus, it is suggested that medication selection would be on an individual basis. Personalized medicine that includes personalized genetic risk score and individualized environmental exposure may have a key role in pathophysiology of osteoporosis [ 98 ].…”
Section: Introductionmentioning
confidence: 99%